The Photophysics of Nucleic Acids: Consequences for the Emergence of Life. Issue 1 (9th November 2022) - Kufner, Corinna L.; Bucher, Dominik B.; Sasselov, Dimitar D.
Abstract: Absorption of ultraviolet (UV) radiation can trigger a variety of photophysical and photochemical reactions in nucleic acids. In the prebiotic era, on the surface of the early Earth, UV light could have played a major role in the selection of the building blocks of life via a balance between synthetic and destructive pathways. As nucleic acid monomers assembled into polymers, their survival and facility for non‐enzymatic replication hinged on their photostability and the ability for self‐repair of lesions, e. g., by UV‐induced charge transfer. Such photoprocesses are known to be sequence‐dependent and could have led to an additional prebiotic selection of the genetic sequence pools available to the earliest life forms. This review summarizes the photophysical processes in nucleic acids upon the absorption of a UV photon and their implications for chemical and genetic selection at the emergence of life and the origin of translation. Abstract : Photochemical reactions in nucleic acids induced by ultraviolet (UV) radiation could have played an important role in the prebiotic selection of the building blocks of life. This Review summarizes the quantum efficiencies of the photorelaxation pathways of nucleic acids and discusses its implications for the emergence of an initial sequence pool on early Earth.